Understanding Factors Influencing Citizens’ Adoption of e-Government Services in the Developing World: Jordan as a Case Study - Mofleh, Samer Ibrahim; Wanous, Mohammed (INFOCOMP Journal of Computer Science, 2008)
Developing countries have established promising e-Government initiatives with the objective of enhancing the accessibility of government services and information for their citizens. However, governments tend to design and launch online services based on their understanding of what citizens need, surprisingly, without actually measuring what increases citizens’ willingness to adopt web-enabled services. Governments must first understand variables that influence citizens’ adoption of e-Government in order to take them into account when delivering services online. The lack of systematic demand-side studies leaves governments with almost no information on how exactly to channel their efforts and financial resources in this area. The main objective of this paper is to examine the variables “needs” that influence citizens’ adoption of e-Government services in Jordan. A sample of 660 people representing the Jordanian e-Society responded to an online survey to identify important variables that governments must consider when delivering services online